KNOW YOUR NFTS - Dimitris Kafteranis; Huseyin Unozkan; Umut Turksen (International Journal of Law in Changing World, 2023)
Non-Fungible Tokens (NFTs) is a new virtual asset phenomenon the trade of which has spread quickly without any regulation. NFTs started as a form of digital art, as a podium for non-famous artists to trade their artwork. Their price skyrocketed when in 2021 Beeple sold his NFT “Everydays – The First 5000 Days” for $69 million at Christies in New York. Since then, NFTs have featured in several business sectors from the sport to the music industry. This expansion has happened in a legal vacuum as no legislation has been adopted in the EU, USA or the UK where the majority of NFT trading takes place.  Concerns have been raised about NFTs and their relation to fraud and money laundering. For example, the Financial Action Task Force (FATF) has recently added them to the list of sectors susceptible to facilitate financial crimes. Recent cases across the world confirm these concerns. For example, in February 2022, the United Kindom (UK) tax authority seized NFTs as part of a VAT fraud; in June 2022, the prosecutors in the United States of America (USA) charged an ex-openSea employee for insider trading and money laundering; and in the same month, the Belgian police seized NFTs as part of an organised money laundering scheme. Anonymity and price volatility of NFTs create a unique and profitable asset for criminals. The complex nature and uncertain legal status of NFTs further complicate the counter measures one can take against illicit use of NFTs.